Chronic venous disease, platelet and haemostatic abnormalities contribute to the pathogenesis of pigmented purpuric dermatoses. (June 2022) - Parsi, Kurosh; Kim, Burcu; O'Connor, Alicia A; Kadam, Pooja; Connor, David
Background: To investigate the aetiology of pigmented purpuric dermatoses (PPD). Methods: 63 patients with a provisional diagnosis of PPD were assessed. Skin biopsies were performed to confirm the clinical diagnosis. Haemostasis was assessed using platelet function analyser-100 (PFA-100), light transmission aggregometry (LTA), impedance aggregometry (Multiplate) and measurement of clotting times and clotting factors. Chronic venous disease (CVD) was assessed by duplex ultrasound. When not contraindicated, patients were advised to discontinue haemostatic-modifying drugs or supplements for 4 weeks after which the laboratory measurements were repeated and the clinical resolution of PPD was assessed. Subsequently, a cohort of patients identified with CVD underwent endovenous interventions and further resolution of PPD was assessed. Results: CVD was found in 48 patients (76.2%) while haemostatic abnormalities were found in 36 (57.1%). 30 patients (47.6%) had concurrent CVD and haemostatic abnormalities. Modifiable risk factors such as the intake of platelet inhibitors or other drugs and supplements such as fish oil were identified in 53 patients (84.1%). These could be ceased in 35 patients of whom 28 (80.0%) achieved either complete or partial resolution of PPD. Treatment of the underlying CVD was performed in 18 patients resulting in complete or partial resolution in 17 (94.4%). In seven patients (11.1%), no CVD or haemostatic abnormalities were identified, and the risk factors included dietary factors such as excessive caffeine or soft drink consumption. Conclusion: Haemostatic abnormalities and CVD contribute to the pathogenesis of PPD. Resolution of PPD in the vast majority of patients may be achieved by cessation of modifiable risk factors and in particular platelet-modifying drugs or supplements and treatment of the underlying venous disease.